Tingkat Keterampilan Passing, Dribbling, Long Passing, Shooting Dalam Permainan Sepak Bola - Kuswiranto, Ragil; Zakky Mubarok, Mochamad; Oktrian, Seni (CV. Multi Kreasi Media, 2024)
The aim of this research is to determine the level of passing, dribbling, long passing and shooting skills in football games. The research method used in this research is descriptive research method. The population and sample in this study were 25 West Bandung Regency Persikabbar players. The sampling technique is using saturated samples, the research used in this research. Passing, Dribbling, Long passing, Shooting skills test in Football Games. The results of this research are passing in the